Penerapan Model Pembelajaran Kooperatif Tipe Rotaring Trion Exchange untuk Meningkatkan Hasil Belajar Matematika Kelas VIII-I UPT SPF SMP Negeri Pantai Labu Semester II Tahun Pelajaran 2021/2022 - Kamila Harahap (Tematik: Jurnal Penelitian Pendidikan Dasar, 2023)
This study aims to see the results of learning mathematics through the application of the Rotating Trio Exchange model to class VIII-1 students of SMP Negeri 3 Pantai Labu. The subjects of this study were all 32 students in class VIII-1, consisting of 15 boys and 17 girls. This research was conducted in 2 cycles. Each cycle is carried out in 2 meetings. The initial data comes from the value document owned by the researcher, namely the results of daily tests. In the initial conditions, the results of learning mathematics for class VIII-1 students averaged 61.3 with a proportion of mastery learning of 44% (14 people). While the learning completeness requirements were determined based on the KKM score of 70. The results of the research in cycle I showed an increase in learning outcomes in mathematics, namely: an average score of 81 with a proportion of mastery learning of 66% (21 people). The results of the first cycle showed that this research was not successful. Because research success is determined if students can complete learning by 75%. Research failure in cycle I became the basis for conducting research in cycle II. After learning improvements were made, the results of learning mathematics in cycle II increased, namely the average value of 89 with a proportion of mastery learning of 91% (29 people). Because the proportion of learning completeness in cycle II has exceeded the success indicators of this study, it can be interpreted that the application of the Rotating Trio Exchange type cooperative learning model can improve student learning outcomes for class VIII-1 UPT SPF SMP Negeri 3 Pantai Labu Semester I Academic Year 2021/2022.